Parents' Expectations and Their Relevance to the Character Education Program in Pesantren - Hermawan, Hermawan (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study aims to analyze parental expectations for character education at Pesantren Darul Arqam Garut, evaluate the relevance of the character education program to these expectations, and propose recommendations for developing a responsive curriculum. Employing a qualitative approach with a case study method, data were collected through observation, interviews, document analysis, and questionnaires from 72 parents, 5 administrators, and 10 educators. The findings indicate that parents expect the formation of Islamic character, discipline, exemplary behavior, staff hospitality, and active involvement through parenting programs. The character education programs, such as Teenage Morality Development, Anti-Bullying Training, and Islamic Parenting Class, are highly relevant to these expectations, supported by religious habituation and the values of KH. Insan Padi. However, parental involvement shows the lowest satisfaction rate (85.7%), indicating the need for increased frequency and variety in parenting programs. The program's relevance to parental expectations strengthens the pesantren's role as a trusted institution for character education. Recommendations include enhancing the intensity of parenting classes, providing hospitality training for staff, and improving inter-institutional coordination. This study contributes to the development of a pesantren-based character education model aligned with the needs of families and society.